(untitled) (Research, Society and Development, 2020)
The purpose of this report is to describe an unusual case of mechanical intestinal obstruction (IOM) in a dog, caused by pequi (Caryocar brasiliense), which resulted in the patient’s death, describing the findings in the physical exams, diagnostic aid and necroscopy. IOM is a frequent cause of emergence in veterinary medicine for small animals. It is usually caused by foreign bodies ingested by the animal. As a methodology, a five-year-old dog reported a history of weight loss and anorexia for three days, in addition to frequent vomiting. The results and discussion showed an abdominal ultrasound examination with an oval-shaped structure, measuring about 3.5 cm in length, forming a strong acoustic shadow, with the presence of segmental dilation in the anterior intestinal portion. The radiographic examination showed segments of dilated intestinal loops and filled with gas, with the presence of an oval-shaped radiopaque structure, with dimensions of 2.7 x 1.5 cm, in the region of the small intestine, close to the bladder. The necropsy exam confirmed the location of the foreign body in the proximal portion of the jejunum, already identified by imaging exams, in the case of pequi (Caryocar brasiliense). It was possible to conclude that the pequi seed proved to be a considerable etiological agent of IOM, although there are no other reports.